Immobilization of Sb in a smelting residue by micro-sized zero-valent iron: Long-term performance under accelerated exposure to strong acid rain. (March 2022) - Zhang, Ying; Lu, Xuxing; Yu, Rongda; Li, Jining; Wang, Fenghe
Abstract: This study investigated the long-term leachability of antimony (Sb) in a smelting residue immobilized by three commercial micro-sized zero-valent iron (ZVI) products. Effect of oxic incubation time (14 days and 120 days) on the immobilization efficiency of Sb were compared, and the long-term leaching risk was evaluated by an accelerated exposure test, in which the slag was consecutively extracted by simulated strong acid rain (SSAR, HNO3 : H2 SO4 = 1:2, pH = 3.20). Notably, all ZVI treatments efficiently immobilized the Sb in this slag in a short term (14 days); the one-step SSAR-leached Sb was reduced by 89%–91% compared to the original slag (5.9 mg/L) and was far below the environmental standard (0.6 mg/L) established by the US EPA. The sequential SSAR leaching results reflected that the 14-d incubated slags after ZVI treatments had strong H + resistance, and the immobilized Sb was not easily activated by continuous SSAR corrosion. The binding of Sb with amorphous phase Fe oxyhydroxides (e.g. ferrihydrite) derived from ZVI corrosion played a dominant role in the Sb immobilization efficiency. However, the longer aging process (120 days) easily resulted in the reduction of Sb immobilization by ZVI treatments. The changes in crystallinity of Fe oxyhydroxides (transformation from poorly-crystalline to crystalline ones) and the pH elevation to alkaline range might explain the weakening of the immobilization of Sb in ZVI-amended slags with 120 days of incubation. In total, the effectiveness of Sb immobilization in smelting residue greatly depended on the type of ZVI and the aging process. Our work has demonstrated that the ZVI treatment was potentially feasible to mitigate the Sb leaching risk from smelting slags; however, the ZVI type needs to be carefully selected and its long-term performance should be adequately verified before practical application. Graphical abstract: Image 1 Highlights: Application of micro-sized ZVI for Sb immobilization in smelting residue. The aging time resulted in the deviation of immobilization efficacy. Different types of ZVI differed in immobilization effectiveness. The Sb was mainly immobilized by amorphous Fe oxyhydroxides from ZVI corrosion.